Effect of the acrylic occlusal device on the stress distribution in the external hexagon implant in situations of dental tightening. A 3D finite element analysis (Research, Society and Development, 2021)
The aim in the present study was to analyze the stress in the external hexagon implant (EH) in a situation of parafunction on three-unit implant-supported prostheses with and without the use of the acrylic occlusal device (AOD) using three-dimensional (3D) finite element analysis (FEA). Eight 3D models referring to the posterior maxilla with three EH supporting single and or splinted screwed metal-ceramic restoration and use of the AOD. AOD was modeled with a thickness of 2 mm. EHs were analyzed using von Mises criteria in the ANSYS 19.2 program. AOD showed to be effective in reducing stress in the EH. However, the use of the AOD was not effective enough to suggest the non-splinting of EH dental implant. The association of splinting and the use of an AOD in the posterior region of the maxilla may be an effective way to decrease the stress in the EH implant in a situation of parafunction.